The relationship between center of pressure displacement and estimated instability of dancers and non-dancers while in a moving room - Schanfein, L.; Rietdyk, S. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Balance is an innate aspect of dance, which leads one to believe that dancers receive "balance training" (Schmit et al., 2005) in the process of developing their technical and artistic abilities. Dancers are significantly less stable than controls when proprioceptive information is unreliable (Simmons, 2005), and they are only more stable than controls when standing with eyes closed (Perrin et al., 2002) suggesting that dancers are less dependent on vision than non-dancers. It may be that, through dance training, dancers are able to maintain postural control when reliance on the visual system is jeopardized by more effectively distributing sensory weightedness away from the visual system to the proprioceptive and/or vestibular sensory systems. If such adaptation occurs, the dancer would be less susceptible to illusions of self-motion induced by a moving visual surround (called vection) than controls but potentially unable to utilize stationary references within an advantageous distance to further aid postural stabilization. The current project proposes to examine if balance control is altered and vection reduced by the addition of stable visual references, in central and/or peripheral vision, within a moving visual surround. Additionally, it will examine if vection, measured as estimated instability, is correlated to center of pressure (COP) displacement.